Case-Based Study of Three Tourism-Dependent Islands in the Philippines The Cases of Boracay Island, Aklan; Puerto Galera, Oriental Mindoro; & Coron, Palawan in the Philippines - Santos, Romeo B.; Tomeldan, Michael V. (MUHON: A Journal of Architecture, Landscape Architecture, and the Designed Environment, 2009)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} This study looked into how three popular tourism island destinations in the Philippines respond to the challenge posed by the changing nature of tourists.   The paper proposes a knowledge representation model to illustrate and explain the complex process between the tourists’ consumption of a place and how the influences emanating from it manifest in the local contexts of culture and the environment of the island destinations. Following the pattern set by the model, the case study identifies manifestation of effects both in the physical and non-physical aspects of the local cultural landscape and the spatial character of the environment of the islands.   It recommends further probe on this subject.